2022
DOI: 10.1177/11795549211036898
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Fibrosis in Patients with Head and Neck Cancer: A Review of Pathogenesis and Clinical Outcomes

Abstract: Radiotherapy-related fibrosis remains one of the most challenging treatment related side effects encountered by patients with head and neck cancer. Several established and ongoing novel therapies have been studied with paucity of data in how to best treat these patients. This review aims to provide researchers and health care providers with a comprehensive review on the presentation, etiology, and therapeutic options for this serious condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 84 publications
(126 reference statements)
1
11
1
Order By: Relevance
“…Therefore, the decrease in CBT-induced myogenic potential and increase in skeletal muscle fibrosis, indicates the increased proliferation capacity of fibroblasts. Radiation-induced acceleration of fibrosis has been reported frequently in human clinical cases in various tissues, such as the lungs [6,23], kidneys [24], and skin [25]. This has also been observed previously in animal models [26][27][28].…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, the decrease in CBT-induced myogenic potential and increase in skeletal muscle fibrosis, indicates the increased proliferation capacity of fibroblasts. Radiation-induced acceleration of fibrosis has been reported frequently in human clinical cases in various tissues, such as the lungs [6,23], kidneys [24], and skin [25]. This has also been observed previously in animal models [26][27][28].…”
Section: Discussionsupporting
confidence: 66%
“…Higher prevalence of dysphagia was found in this study (31%) compared to the previously reported prevalence of 14% at 2 years [56]. This may be due to development of soft tissue fibrosis, which tend to progress over time [31,57]. The finding of this study is of great importance as literature on long-term patient-reported dysphagia is scarce.…”
Section: Discussioncontrasting
confidence: 45%
“…Cytokines such as interleukin (IL)-1 beta (IL-1β), IL-6, IL-8, and tumor necrosis factor (TNF) have been linked to oral mucositis, and possibly xerostomia, during RT, manifested by elevated levels in saliva immediately after treatment in HNC patients [29,30]. Chronic inflammation may further cause fibrosis, one of the key pathological features in radiation-induced late effects such as dysphagia [4,31]. Transforming growth factor beta (TGF-β) and TNF are involved in the formation of fibrosis in irradiated tissue, predominantly found in lung cancer studies [4,[32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…65,66 A most potent impact of radiotherapy is on the TME fibroblasts, subsequently to vascular damage and leakage of serum proteases, leading to extracellular matrix remodeling, fibroblast activation, and fibrosis. 67 Activated fibroblasts produce and organize large amounts of collagen in dense fibrillary tissue with opposing actions on residual tumor survival: increased hypoxia and decreased access to nutrients versus increased cancer cell survival due to integrin 1 signaling and TGF-1 release. 67 Antibody-mediated TGF-β neutralization during radiation therapy effectively generated carcinomas regression in mice and in humans, provided co-administration of anti-PD-1 and anti-CD137 (TNF receptor superfamily member 9) immunostimulatory monoclonal antibodies.…”
Section: Stroma and Microenvironment Impact On Radiation-treated Tumorsmentioning
confidence: 99%
“…67 Activated fibroblasts produce and organize large amounts of collagen in dense fibrillary tissue with opposing actions on residual tumor survival: increased hypoxia and decreased access to nutrients versus increased cancer cell survival due to integrin 1 signaling and TGF-1 release. 67 Antibody-mediated TGF-β neutralization during radiation therapy effectively generated carcinomas regression in mice and in humans, provided co-administration of anti-PD-1 and anti-CD137 (TNF receptor superfamily member 9) immunostimulatory monoclonal antibodies. [68][69][70] However, several clinical trials concluded that patients eventually relapse, and that all these treatments ended by being ineffective.…”
Section: Stroma and Microenvironment Impact On Radiation-treated Tumorsmentioning
confidence: 99%